Nitrogen Fertilizers and Plant Spacing in Organic Rice Cultivation: A Review - Erythrina Erythrina; Gagad Restu Pratiwi; Nurwulan Agustiani; Arinal Haq Izzawati Nurrahma (Green Engineering Society, 2023)
Organic rice cultivation is one of the technologies developed in Indonesia around two decades ago, but it is not growing as expected. Indeed, organic rice production is considered less effective than conventional farming. This review article explores the role of agronomic factors in organic rice cultivation related to organic nutrient availability and plant spacing. The proposed alternative solutions for using organic inputs to improve soil fertility and increase crop yields are also discussed. The effectiveness of organic fertilizers to chemical fertilizers based on the Rice Agro-advisory Service shows that organic rice has lower yields than conventional farming. The yield reduction ranges between 0.5 and 2.2 t ha−1 or around 9 to 43%, depending on organic amendments and site characteristics. It is also proven that applying high-nitrogen nutrients from organic fertilizers does not increase rice production. Application of nitrogen fertilizers in the right amount and at the correct plant stage is more essential because it affects the yield component of rice plants. Narrower plant spacing in transplanted organic rice results in higher productivity. An increase in plant population higher than 25 hills m−2 no longer significantly increases rice yields. Among the agronomic factors that affect organic rice cultivation are the diversity of organic amendment in nutrient mineralization, especially nitrogen, according to plant needs, and narrow plant spacing that allows lesser weeds to grow among crop plants. These two agronomic factors need to be considered and applied by farmers to get the optimum growth and yield of organic rice cultivation.